2018
DOI: 10.1002/maco.201810366
|View full text |Cite
|
Sign up to set email alerts
|

Protection of copper by treatment with hot vapors of octadecylamine, 1,2,3‐benzotriazole, and their mixtures

Abstract: The possibility of creating an effective technology for protecting copper products by treatment with vapors of low‐volatile corrosion inhibitors at elevated temperatures is demonstrated for the first time. It is shown that 1‐h treatment with vapors of octadecylamine or its mixture with 1,2,3‐benzotriazole at t = 100 °C results in the formation of ultra‐thin hydrophobic adsorption films, markedly increases the corrosion resistance of copper, and can be used for temporary protection of metal products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 21 publications
2
24
0
6
Order By: Relevance
“…The techniques for sample preparation and measurements, the purity of the compounds and the materials used in this study are similar to those reported previously [13].…”
Section: Methodsmentioning
confidence: 65%
See 3 more Smart Citations
“…The techniques for sample preparation and measurements, the purity of the compounds and the materials used in this study are similar to those reported previously [13].…”
Section: Methodsmentioning
confidence: 65%
“…The increase in ChIn efficiency with an increase in their p 0 values indicates that equilibrium adsorption of BTA derivatives on copper is not reached in 1 h of chamber treatment at 100°C. It should be reminded that the choice of this duration for the CT is based on data [13] that the PAE of BTA stabilizes after chamber treatment for 20-40 minutes. However, rather a narrow range of CT durations (up to 1 h) was considered in this study.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Development of the chamber treatment method was intensely performed for the past three years, and CINs suitable for the protection of monometallic products made of steel, copper, aluminum alloys, magnesium and zinc [4][5][6][7] have already been found. However, versatile CINs capable of simultaneously protecting several metals and alloys are not yet available.…”
Section: Introductionmentioning
confidence: 99%